Cultura, sensibilidade e comunicação intersensorial: as festas das aparelhagens no Estado do Pará - CASTRO, Marina Ramos Neves de (Associação Nacional dos Programas de Pós-Graduação em Comunicação, 2022)
The article proposes to think about the Festas de Aparelhagem (sound system parties), traditional festive events in the state of Pará, based on its technological dimension and thus, as dynamics of creation, production and sensory reverberation. Based on an ethnographic research and reflecting on the importance of the technological devices present in the sound systems, we seek to understand the intersensory communication present in these events and, in the same way, the meanings of culture and intersubjectivity. Along this path, the relationship between communication, culture, technology and sensoriality is discussed using Le Breton (2016a; 2016b), Laplantine (2017) and Anonimizado (2018). Miller (2008; 1998) and Gonçalves (2007) are also used to reflect on the material culture produced around the technological artifacts of parties and Anonimizado (2020) to debate the issue of intersensory communication.